Rational Design, Synthesis, In Vitro, and In Silico Studies of Dihydropyrimidinone Derivatives as β-Glucuronidase Inhibitors - Somaye Karimian; Yasaman Moghdani; Mahsima Khoshneviszadeh; Somayeh Pirhadi; Aida Iraji; Mehdi Khoshneviszadeh (Journal of Chemistry)
In the current study, a series of dihydropyrimidinone derivatives were rationally designed as β-glucuronidase inhibitors. These designed compounds were successfully synthesized and characterized through various spectroscopic techniques such as IR, 1H-NMR, 13C-NMR, and EI-MS. A structure-activity relationship (SAR) of synthesized derivatives to inhibit β-glucuronidase was also established. In vitro biological evaluations revealed that 4i as the most potent compound in this series has an IC50 value of 31.52 ± 2.54 μM compared to the standard D-saccharic acid 1,4-lactone (IC50 = 41.32 ± 1.82 µM). Also, molecular docking and dynamics studies of the most potent compound are performed to evaluate interactions between the active compound and binding site.